(untitled) (UNWE Yearbook, 2024)
This paper presents a retrospective analysis of the development of accounting education in France. The study encompasses the regulatory framework applied in the higher education institutions where education in accounting is available. Both specialized higher schools and universities of broad education profile come within the survey. The main method employed is the method of description and analysis of the contents of publicly announced academic documentation available on the websites of these higher education institutions. The results are uniformity of Bachelor’s degree programmes to a considerable extent and classification of Master’s degree programmes according to the future professional realization of students. The tendencies towards lack of foreign students and reduced interest to programmes in French are highlighted as major areas of concern.